High‐dose, short‐term corticosteroids for ARDS caused by COVID‐19: a case series - So, Clara; Ro, Shosei; Murakami, Manabu; Imai, Ryosuke; Jinta, Torahiko (Respirology case reports, 2020)
We report a case series of seven mechanically ventilated patients with acute respiratory distress syndrome (ARDS) caused by coronavirus disease (COVID‐19) who received early treatment with high‐dose, short‐term systemic corticosteroids to prevent cytokine overproduction. Of the seven patients, four were male and median age was 69 years. They were intubated within seven days after admission when their respiratory status rapidly worsened. At that time, we administered 1000 or 500 mg/day for three days of methylprednisolone intravenously, followed by 1 mg/kg and tapered off. The median duration for the total administration of corticosteroids was 13 days. This high‐dose, short‐term corticosteroid therapy enabled extubation of the patients within seven days. Many questions on the clinical management of COVID‐19 remain unanswered, and data on corticosteroid therapy as a choice of treatment are mixed. We present the clinical course of our cases, review the previous evidence, and discuss management. Many questions on the clinical management of coronavirus disease (COVID‐19) remain unanswered, and data on corticosteroid therapy as a choice of treatment are mixed. We present the clinical course of seven patients, review the previous evidence, and discuss management.